Failed Tracheal Intubation During Obstetric General Anaesthesia: A Literature Review. Issue 3 (September 2016) - Kinsella, S.M.; Winton, A.L.; Mushambi, M.C.; Ramaswamy, K.; Swales, H.; Quinn, A.C.; Popat, M.
Abstract : ( Int J Obstet Anesth. 2015;24(4):356–374) Failed tracheal intubation guidelines for obstetrics were first developed by Michael Tunstall at Aberdeen Maternity Hospital in the 1970s. Multiple versions of these original guidelines spread through local adaptation. The American Society of Anesthesiologists produced official national guidelines on management of the difficult airway in 1992, and these were last updated in 2013. Similar guidelines were developed by the Difficult Airway Society (DAS) for the United Kingdom in 2004. These do not address issues specific to the obstetric patient, however. Developments in obstetric anesthesia practice that have taken place since Tunstall introduced his guidelines include availability of supraglottic airway devices (SAD), antacid and oral intake protocols during labor, rapid onset nondepolarizing neuromuscular blocking drugs, and rapid neuromuscular reversal agents. Use of neuraxial anesthesia for cesarean section has increased, and up to one third of obstetric general anesthetics are now administered after failed neuraxial anaesthesia. The Obstetric Anaesthetists' Association (OAA) and DAS have just published stand-alone obstetric failed intubation guidelines. The primary aim of this study was to search the relevant literature for evidence to support these guidelines, with special focus on quantitative data to estimate incidences of difficult airway management, management options, and maternal and neonatal outcomes.